Surface ocean CO2 in 1990–2011 modelled using a feed‐forward neural network. (July 2015) - Zeng, Jiye; Nojiri, Yukihiro; Nakaoka, Shin‐ichiro; Nakajima, Hideaki; Shirai, Tomoko
<x xml:space="preserve">Abstract</x> This dataset includes the monthly distributions of CO2 fugacity in the world surface oceans reconstructed using a feed‐forward neural network model and the CO2 measurements of the Surface Ocean CO2 Atlas version 2.0. It has a spatial resolution of 1 × 1° and spans a period of 22 years, from January 1990 to December 2011. The dataset also includes necessary parameters for the reconstruction and an estimate of the CO2 fluxes between the ocean and the atmosphere. The aim of this work is to provide a dataset for estimating the oceans' contribution to the global carbon budget.